Private Participation in Electricity : The Challenge of Achieving Commercial Viability and Improving Services - Tenenbaum, Bernard; Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
This document is about the private participation in electricity. Private activity in electricity in developing countries has stabilized at a modest level since 2001. Private activity also became more evenly distributed between International Development Association (IDA) countries and non IDA countries. Private activity in electricity remained concentrated in a few countries. Investors generally prefer greenfield projects structured as enclave projects, protected from many sector risks. Electricity is not the only infrastructure sector where this type of private investment predominates. Similar arrangements have emerged in water and sanitation, where greenfield water and sewage treatment plants sell to a single customer through government-supported take or pay agreements. Distribution is inherently riskier for investors because it involves selling to thousands of customers who purchase at prices that are highly visible and politically contentious. To attract investment in distribution, a new guarantee mechanism has been adopted. In overview, these projects usually provide protection from major risks through long-term contracts and often come with government payment guarantees. If there is to be significant and sustained private investment beyond greenfield generation projects, it will need to be built on a platform of commercially viable electricity distribution entities. If private participation can establish such entities, it will create the best foundation for future upstream private investment in generation.